2015
DOI: 10.1186/s12971-015-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived benefits and health risks of cigarette smoking among young adults: insights from a cross-sectional study

Abstract: BackgroundPerceptions of smoking-related health risks and benefits among young adults (18–24 years) and their smoking behaviour have not been adequately studied in low-income countries like Nepal. This study has examined the perceived risks and the benefits of smoking among young adults who smoke vs. don’t smoke.MethodsA cross-sectional study was carried out from August to September 2013 among 315 young adults (18–24) from four conveniently selected private colleges of different faculties in Kathmandu Metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
4
13
2
1
Order By: Relevance
“…Comparatively, lower prevalence rates were reported among university students studying in South Africa 18.6% (Senkubuge et al, 2012), United States of America 20% (Eissenberg et al, 2008), Malaysia 30% (Al-Naggar and Saghir, 2011) and Turkey 32.7% (Poyrazoğlu et al, 2010). A higher prevalence reported in the present study may be attributed to the non-standardized criteria for shisha smokers (anyone who had smoked shisha in last 30 days is considered as a current shisha smoker) (Aryal and Bhatta, 2015;Habibullah et al, 2013), as well as to the cultural and social acceptance to shisha smoking in the UAE (Kader, 2010;Athamneh et al, 2015). For this reason, the results of this study categorized shisha dependency students from current shisha smokers as shisha dependency students are vulnerable for various physical and mental health problems.…”
Section: Discussioncontrasting
confidence: 60%
“…Comparatively, lower prevalence rates were reported among university students studying in South Africa 18.6% (Senkubuge et al, 2012), United States of America 20% (Eissenberg et al, 2008), Malaysia 30% (Al-Naggar and Saghir, 2011) and Turkey 32.7% (Poyrazoğlu et al, 2010). A higher prevalence reported in the present study may be attributed to the non-standardized criteria for shisha smokers (anyone who had smoked shisha in last 30 days is considered as a current shisha smoker) (Aryal and Bhatta, 2015;Habibullah et al, 2013), as well as to the cultural and social acceptance to shisha smoking in the UAE (Kader, 2010;Athamneh et al, 2015). For this reason, the results of this study categorized shisha dependency students from current shisha smokers as shisha dependency students are vulnerable for various physical and mental health problems.…”
Section: Discussioncontrasting
confidence: 60%
“…They perceived a positive benefit in consuming tobacco such as gaining more friends or becoming more relaxed. These considerations are similar to those reported in previous studies [9][10]12,[42][43].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies characterize college as a period of smoking transitions, including smoking initiation and smoking consolidation [6][7][8]. Although most college students believe that they are going to stop smoking before 30 or upon becoming parents [9][10], 30% of them will have difficulty in quitting and will remain addicted for decades [11].…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Studies in non-IBD populations have found that smoking initiation is more likely when there is a perceived short-term benefit, despite acceptance of short-and long-term risks. 58,59 Our findings should therefore embolden clinicians to advise against smoking and reassure patients who already smoke that they can benefit from the many advantages of smoking cessation without risk of worsening their UC.…”
Section: Discussionmentioning
confidence: 84%